Index Whittaker transform for Boehmians - Maan, Jeetendrasingh; Prasad, Akhilesh (Indian journal of pure and applied mathematics, 2024)
In this paper, we introduce the index Whittaker transform as a continuous linear map from one space of Boehmian into another. The index Whittaker transform is further investigated for the compactly supported distributions.